Colorectal cancer and environmental pollution - Gulis, G; Fitz, O; Wittgruber, J; Suchanová, G (Central European journal of public health, 1998)
Monitoring of personal exposure of population from environmental pollution is a very complicated process. There are many different pollutants in environment in very low concentrations and their distribution is non-homogenous. To measure these pollutants is not often feasible or possible due to technical problems. On the other side these can influence the health status of inhabitants by the way of a long time exposition by low doses. In our work we studied an incidence of the cancer of colon and rectum in rural area of Trnava district during the years 1986-1995. These are the most frequent types of cancer in our district-13.4%, incidence rate is 27.5 per 100,000 inhabitants. The standardised incidence ratio (observed/expected cases) were calculated for all villages, including statistical parameters. The population in this small area (1390 km2) is relatively stabile from point of view of migration and nutritional habits. The urban area consisting from five towns was excluded from analysis because the life style and nutritional habits of people living in towns and villages are different. These suppositions enabled to concentrate our attention to the study of environmental factors which can influence development of the colorectal cancer. The SIR's were correlated with time of public drinking water supply, surface water quality, location of waste dumps, and time of gas heating using as kind of house heating. Positive and statistically significant correlation's were found between SIR of the colorectal cancer and waste dump location for females and weaker for surface water and SIR for males. Statistically significant elevation of SIR both for males and females were found in one village. Ecological design of study did not allow to study confounders, yet served enough information for preparation of analytical studies and public health decision-making process on local level.
Keywords: lineární modely; Humans; Confidence Intervals; Environmental Monitoring; Female; interval spolehlivosti; rizikové faktory; lidé; Slovakia; Slovenská republika; látky znečišťující životní prostředí; pilotní projekty; Pilot Projects; monitorování životního prostředí; venkovské obyvatelstvo; Environmental Pollutants; ženské pohlaví; kolorektální nádory; Male; Epidemiological Monitoring; Linear Models; incidence; Incidence; Rural Population; epidemiologické monitorování; mužské pohlaví; Colorectal Neoplasms; Risk Factors